Scenario of pulses production in India - Dixit, G P; Srivastava, A K; Ali, Hasmat (Indian Farming, 2024)
Pulses are the backbone of Indian agriculture due to their significant role in human and animal nutrition, soil ameliorative properties, environmental sustainability and economic viability. India is the largest producer, processor, importer and consumer of pulses in the world with more than 12 major and minor pulses cultivated over 29-30 million ha. The country witnessed production of 26.05 million tonnes of pulses during 2022-23. This article deals with scenario of pulse production, import-export status, yield gap and delineates constraints along with strategies to overcome these constraints.